Hubungan Penyesuaian Diri dengan Keterampilan Problem Solving pada Siswa Kelas VII SMP - Nahak, Maria Sariani; Upa, Muhammad D. P.; Apriliana, I Putu Agus (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
This study aims to determine the relationship between self-adjustment and problem-solving skills of students in grade class VII at middle school (SMP Negeri 5 Kupang). This study uses a quantitative approach with a correlational study. This research involved a population of 323 students at SMP Negeri 5 Kupang City. The sampling technique used was proportional random sampling technique and the sample size was 63 students. Data collection techniques use instruments that measure self-adaptation and problem-solving skills with a 4-point Likert scale model. Data were analyzed using correlational analysis techniques with the help of the IBM SPSS version 25 program. The results of this research show that self-adjustment and problem-solving skills among students in grade class VII have a significant and positive relationship where the calculated r-value > r table (0.465 > 0.248). These findings inform that students' self-adjustment is an important part of students' problem-solving skills in carrying out academic activities in a new school environment.